Financial deepening and equity investment in emerging markets - Omodero, Cordelia Onyinyechi; Adeyemo, Kingsley Aderemi; Ekundayo, Olugbenga; Onyekachi, Silvia Nwakaego; Omesue, Chukwudi Emmanuel (Asian Economic and Financial Review, 2023)
The aim of this study is to examine the effect of financial deepening on stock market development using equity investment. There is an increasing need for financial service expansion to improve equity investment, which will lead to better stock market operations. We identify the key financial deepening mechanisms in this study, such as broad money supply, credit to the private sector, and economic progress, and we use inflation as a moderating tool. The study spans the years 1981 through 2021. Because of the unit root result, we believe that the autoregressive distributed lag (ARDL) model and error correction model (ECM) are the most appropriate techniques for producing the most reliable results. The study's findings show that, in both the long and short runs, GDP has a positive impact on equity investment, implying that an improvement in the general economic situation can have a positive impact on equity investment. Similarly, in the short run, broad money supply has a positive and significant influence on equity investment, but not in the long run. Credit to the private sector, on the other hand, has a material negative effect on stock market development in the short run and becomes insignificant in the long run. These findings suggest that the government should pay closer attention to financial deepening indicators in order to improve equity investment, which is a major component of stock market capitalization. In line with the results, the government should make more funds available for private sector activities while also maintaining a stable money supply to meet economic demands.